Peran Corporate Governance Dalam Meningkatkan Kinerja Keuangan Perusahaan di Sektor Manufaktur - Irsyad Kamal (CV Putra Publisher, 2024)
Corporate governance is a key element in ensuring transparency, accountability, and operational integrity in a company. In the manufacturing sector, the implementation of effective corporate governance is essential to improve the company's financial performance. However, there is still a knowledge gap regarding how corporate governance affects the financial performance of companies in this sector. This study uses a qualitative method with a literature review approach to explore the relationship between corporate governance and financial performance in manufacturing companies. The results of the study indicate that the implementation of good corporate governance can prevent mismanagement, increase transparency and accountability, and integrate values, ethics, and risk management into the company's strategy. In addition, the results of the study also indicate that companies that implement effective governance can increase the trust of investors and other stakeholders, which in turn supports long-term business growth and sustainability. However, many companies still face challenges in implementing strong governance, indicating the need for greater efforts in education and training and the development of better internal control systems. The implications of this study emphasize the importance of companies to strengthen their governance in order to achieve optimal financial performance and long-term sustainability. It provides important contributions both in enriching the academic literature and in providing practical guidance for manufacturing companies to strengthen governance and improve their financial performance. This implication emphasizes the importance of good corporate governance to achieve long-term business sustainability and create value for all stakeholders.